TOKO MODERN DAN TRADISIONAL: KEADILAN REGULASI: TOKO MODERN DAN TRADISIONAL: KEADILAN REGULASI - Muhammad Fahmi Nurani (Jurnal Humaniora Teknologi, 2021)
With the growth of shopping centers, it can be said that every year there are many minimarkets, supermarkets, hypermarkets, and modern markets such as malls whose existence continues to shift traditional markets in cities throughout Indonesia. People in urban areas tend to prefer to shop for their daily needs at supermarkets or supermarkets. The rapid development of shopping centers raises concerns for some people, because the irregular development of modern markets can result in the extinction of traditional markets or small shops due to their declining turnover. The growing retail giant is a threat to traditional markets, distance rules, zoning and the absence of other restrictions. Even now the modern market is side by side with the traditional market. The sustainability of the efforts of domestic producers and SMEs to encourage domestic products to enter the modern retail market is also an important issue to pay attention to.